Dampak Manajemen Kinerja Pegawai Negeri Sipil terhadap Efisiensi Pemanfaatan Anggaran Daerah - Vilzati Juned; Rivat Joniansyah (Jurnal Bina Praja, 2026)
This study examines the association between civil servant performance management and the efficiency of regional budget utilization in the Government of Aceh Province, Indonesia. An explanatory sequential mixed-methods design was employed, combining a quantitative survey of 100 civil servants involved in regional planning, budgeting, financial management, and program evaluation with qualitative interviews of 12 key informants, including budget managers, planning officials, and internal supervisors. Quantitative data were analyzed using multiple linear regression, and qualitative data were examined through thematic analysis to explain the statistical findings. The results indicate that the six dimensions of civil servant performance management are collectively and statistically associated with the efficiency of regional budget utilization, although the explanatory power of the model is relatively modest. At the individual level, financial compliance and outcome orientation are positively and significantly associated with budget efficiency, and timeliness is significantly but negatively associated with it, whereas performance planning, implementation productivity, and monitoring and evaluation show no significant relationship. Qualitative findings suggest that these patterns reflect differences between the substantive and the procedural implementation of performance management practices, particularly regarding fiscal compliance, outcome-focused budgeting, and year-end budget execution. This study contributes to the literature by suggesting that formal performance management systems alone are insufficient to improve regional budget efficiency; rather, efficiency is more closely associated with substantive fiscal compliance, outcome orientation, and implementation quality within decentralized public administration.